ADHERENCE TO SELF-CARE IN PATIENTS WITH NEUROGENIC LOWER URINARY TRACT DYSFUNCTION: INSTRUMENT VALIDATION - Candido, Cínthia Ferreira; Nunes, Alessandra Sant’Anna; Silva, Fernanda Henriques da; Mello, Livia Fajin de; Moraes, Advi Catarina Barbachan; Peres, Ellen Marcia (Cogitare Enfermagem, 2023)
Objective: To build and validate the content of the instrument for adherence to self-care for patients with Neurogenic Lower Urinary Tract Dysfunction who perform intermittent self-catheterization as to appearance and content. Method: Methodological study of instrument content validation, composed of three stages: literature review, instrument construction and instrument validation, respectively. The analysis was performed using the Agree model, and by calculating the content validation index, between 2020 and 2021. Results: Agree II, showed a result of 85.6% and 84.5% for validation of the scope and purpose and stakeholder domains. In content validation, the family history item was removed from the instrument with a content vanity index of 0.77. Conclusion: The instrument will contribute to offering subsidies for professional practice and to patients with the dysfunction.